Measuring direct and indirect tendon parameters to characterize the proximal tendinous complex of the rectus femoris in football and futsal players - Mechó, Sandra; Lisbona Ortega, Raquel; Pruna, Ricard; Nescolarde Selva, Lexa; Morillas Pérez, Jordi; Rodríguez-Baeza, Alfonso; Martínez Agea, Javier; Pérez-Andrés, Ricard (Frontiers in Physiology, 2023)
Objective: To present unprecedented radiological parameters that characterize the angle between the direct and indirect tendons of the proximal rectus femoris (RF) and its inclinations and to evaluate the population variability according to demographic variables. Materials and methods: From September 2019 to July 2021, using MRI multiplanar reconstructions of the proximal thigh/hip, two blinded radiologists measured the direct and indirect tendon angle and the inclination of each tendon in different planes. The intra- and inter-observer agreements were assessed with Bland–Altman analysis and intraclass correlation coefficient (ICC). The correlations between radiological parameters and demographic variables were evaluated using linear regression, Student’s t-test, and analysis of variance. Results: We performed 112 thigh/hip MRI scans on 91 football players of different age, gender, and disciplines (football and futsal). For observer 1 (the reference), the mean direct and indirect tendon angle was 56.74° ± 9.37, the mean indirect tendon slope was −7.90° ± 7.49, and the mean direct tendon slope was 22.16° ± 5.88. The three measurements showed inter- and intra-observer agreement (mean differences ∼0). No correlation was observed between age and the parameters. Likewise, no statistically significant differences were found for gender, dominant limb, examined limb, and sport. Conclusion: There is an inter- and intra-observer agreement in the measurements of the direct and indirect tendon angle and the inclination of each tendon. There is population variability in the proximal tendinous complex unrelated to demographic factors. These results allow further detection of morphological patterns that represent a risk factor for lesions in the RF in professional football and futsal players and other sports.